The Importance of the Role of Guidance Teachers in Overcoming Learning Problems in Class XI Students of SMA 1 Sikur - Aulaq, Minhatul (Journal of Educational Studies, 2024)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their personal potential, personality, intelligence, noble morals, and skills needed by themselves and society (National Education System Law No. 20 of 2003). Education can be achieved through the learning process both in the school environment and outside the school environment. Education is the main foundation that shapes a person's future, and teachers are responsible for determining the potential of their students.(Lesmana, 2021)However, problems that may hinder students' academic and emotional growth are common. The role of a Guidance and Counseling Teacher (BK) is very important when learning problems arise. Counseling teachers, who are often considered unsung heroes in the education system, have a special and important role in supporting student development. They are not just advisors; they are friends, counselors, and liaisons between students, parents, and school employees. This article will discuss the important role played by guidance and counseling teachers in overcoming student learning problems. Counseling teachers play an important role from spotting problems to providing necessary support and resources. in ensuring that all students have equal opportunities to achieve their best potential.(WIRIANI, 2023). This article aims to show the important role of guidance and counseling teachers, provide information about how they help students in dealing with learning difficulties, and show the positive effect they have on educational progress. Let's take a look at the world of guidance and counseling teachers and how they help our students' futures.